PENGARUH TEMUAN KELEMAHAN SISTEM PENGENDALIAN INTERN DAN TEMUAN KETIDAKPATUHAN TERHADAP KETENTUAN PERATURAN PERUNDANG-UNDANGAN TERHADAP OPINI BPK ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Oka Purnawan Widodo; Sudarno Sudarno (Diponegoro Journal of Accounting, 2017)
This study aims to examine the effect of audit findings (weakness of internal control systems and compliance toward laws and regulations) on audit opinion of local government financial reports in Indonesia. Independent variables used in this study, weakness of internal control systems audit findings and non-compliance toward laws and regulations audit findings, proxied by the numbers of audit findings. Whereas for dependent variable is audit opinions consist of ordinal data. This study uses secondary data i.e. local government financial reports published by Badan Pemeriksa Keuangan Republik Indonesia (BPK RI) on the fiscal years of 2013 and 2014. The selection of the sample in this study using the purposive sampling method. Technique of data analysis in this study uses descriptive statistics and ordinal logistic regression to find out the effect of audit findings on audit opinion. The results showed that audit findings, which are weakness of internal control systems audit findings and non-compliance toward laws and regulations audit findings, negative significantly affect the determination of audit opinion on the local government financial reports published by BPK.